Farm Security Administration. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows evacuees being interviewed by a female employee of the Farm Security Administration in a control station at Visalia, California.